Новые электродные материалы в решении проблем водородной энергетики - Тульский, Геннадий Георгиевич; Подустов, Михаил Алексеевич; Сенкевич, И. В.; Тульская, Алена Геннадьевна (НТУ "ХПИ", 2015)
Обоснован выбор материала газодиффузионного электрода для реализации деполяризации анодного процесса при реализации сульфатнокислотного цикла производства водорода. В качестве деполяризатора использован SO₂. Газодиффузионный электрод состоит из пористой основы (графит марки ПГ-50) и покрытия из материалов, показавших каталитическую активность в окислении SO₂ активного углерода (АУ), Pt, RuO₂, MoO₃, WO₃. По каталитической активности исследованные анодные материалы можно расположить в следующий ряд Pt > RuO₂ > MoO₃ > WO₃ > АУ. Установлен синергетический эффект от использования композиции Pt + АУ, нанесенных на графитовую основу, в сравнении с индивидуальными Pt и АУ.

The choice of anodic material for SO₂ – depolarizated hydrogen producing was justified. Gas-diffusion electrode consists of a porous graphite support and the coating materials, which demonstrate catalytic activity in SO₂ oxidation process: active carbon (AC), Pt, RuO₂, MoO₃, WO₃. According to the catalytic activity investigated anode materials can be placed in the following order Pt> RuO₂> MoO₃> WO₃> AC. The synergistic effect of using the composition Pt + AC supported on graphite-hand basis, compared with the individual Pt and AC was determined. The composition of the active coating of the gas diffusion anode, exhibits high kinetic parameters in a wide range of current densities, and a method of its application were proposed. The durability of anode materials has been tested. The results of kinetic studies confirmed the laboratory cell. The possibility of using sulphur-acid method of producing hydrogen for utilization of SO₂. It was determined that the specific energy consumption was 2.6 ... 3.1 kW · h · nm³ H₂ at a current density of 500 ... 1000 A·m⁻². Conducted pilot tests, which proved the feasibility of the depolarization of the anodic process of SO₂ in sulphur-acid method of producing hydrogen.
New electrode materials for hydrogen economy problems solving
Keywords: электрод газодиффузионный; углерод активный; деполяризация; процесс анодный; оксид серы; gas diffusion electrode; active carbon; depolarization; anodic process; sulfur oxide